Writers and the state: heterotopias of exclusion in the works of Sonallah Ibrahim and Gholam-Hossein Sa'edi - El Taraboulsi, Sherine Nabil (AUC Knowledge Fountain, 2011)
In undemocratic regimes, the cultural space is expected to align with the structure of domination, and cultural production is deemed an arm of the state, a vehicle for conformity and indoctrination. Under such circumstances, the personal and artistic choices of writers and artists become highly politicized. This thesis looks at the politics of interaction between writers and the state, specifically focusing on the heterogeneous literary space created by the author in which structures of domination are unveiled, and those placed on the periphery by the state are brought to the center of the literary space. A writer as citizen negotiates his relation to the state by means of his writing thereby practicing a form of cultural activism; the macrostructures of state domination proliferate through the microprocesses of the literary work, and it is this relation that is subject to inquiry. The thesis focuses on two crucial periods in the histories of Egypt and Iran: the period after the 1952 Egyptian Revolution and the period preceding the Iranian 1979 Islamic Revolution; and examines the literary works of two notable writers: the Egyptian Sonallah Ibrahim and the Iranian Gholam-Hossein Sa'edi.